Referred Trigeminal Facial Pain from Occipital Neuralgia Occurring Much Earlier than Occipital Neuralgia - Byung-chul Son (Case Reports in Neurological Medicine)
We report a very rare case in which a patient believed to have auriculotemporal neuralgia due to the repeated recurrence of paroxysmal stabbing pain in the preauricular temporal region for four years developed occipital neuralgia, which finally improved with decompression of the greater occipital nerve (GON). The pain of occipital neuralgia has been suggested to be referred to the frontoorbital (V1) region through trigeminocervical interneuronal connections in the trigeminal spinal nucleus. However, the reports of such cases are very rare. In occipital neuralgia, the pain referred to the ipsilateral facial trigeminal region reportedly also occurs in the V2 and V3 distributions in addition to that in the V1 region. In the existing cases of referred trigeminal pain from occipital neuralgia, continuous aching pain is usually induced, but in the present case, typical neuralgic pain was induced and diagnosed as idiopathic auriculotemporal neuralgia. In addition, recurrent trigeminal pain occurred for four years before the onset of occipital neuralgia. If the typical occipital neuralgia did not develop in four years, it would be impossible to infer an association with the GON. This case shows that the clinical manifestations of referred trigeminal pain caused by the sensitization of the trigeminocervical complex by chronic entrapment of the GON can be very diverse.